Methods for forming social and communication skills in primary school students with limited intellectual communication opportunities (Journal of Educational Sciences, 2022)
The article deals with methods and methods of teaching children with intellectual disabilities to communicate, conducting corrective work, and forming their social and communicative skills. Because through communication, the child gets to know himself and the world around him. This is an urgent problem, adaptation, socialization and training of a child is a complex process. Today, a child with intellectual disabilities needs to learn social skills in order to successfully adapt. Adaptation to social phenomena, socialization is formed only through communication skills. The main thing for a growing person is his character, actions, relationships with people. Through this world, a person goes through different stages of life. Relationships with adults and peers are important in the formation of social and communicative skills of intellectually disabled children through the stages of life. In the period of human development, basic moral values ​​are formed, the process of self-awareness takes place, opportunities for habituation appear.Key words: intellectually disabled child, communication, social-communicative skills, oral communication tools, communication skills, adaptation, socialization